Liberdade cívica, o sonho maquiaveliano - Andrade, Erlan Rodrigues (2013)
Niccolò di Bernardo dei Machiavelli contributed decisively to the development of the ideas of political freedom, under the civic and republican bias. Machiavelli reading and commenting Livy exalted republican Rome and conflicts among the Greats, who dominated , and the people who struggled not to be dominated, which were the cause of freedom in Rome. And from that caused a rupture with the political thought of antiquity and his time, in proclaiming political realism in the modern political analysis. Machiavelli is a unique author in the analysis of civic freedom in proclaiming that the best government is the Republican, the people is the main defender of freedom, that the institutionalization of conflict, not the pursuit peace ideal, can propitiate the civic freedom, among other arguments. The analysis of machiavellian civic freedom focuses on the First Book of the Discourses on the First Decade of Livy, especially in the first 18 chapters, considering forming a theoretical set over the republics. To enter in the Florentine in republican debate, which was a part, seeks to understand some of its main categories: disunity, riots, corruption, people, Greats, theory of humors, republic, verità effetualle, philosophy of history, virtù , fortune , 'human nature', matter and form. Although Machiavelli is a thinker of the sixteenth century, its contribution is sitting in a society where liberal thought achieves its hegemony under a new configuration, which is called neoliberal, that added to globalization and others hegemonic practices generate a series of economic, social, legal, politics and educational measures that minimize, invalidate and prevent conflicts by constructing identities and their justification and legitimation. Machiavelli was the author who through a dream of freedom advocated dialogue, conflict, dissent, that many condemn without pondering and someone that examine well, will discover that they gave rise to good laws, the ordinances beneficial and civic freedom